Management of Workplace Diversity and Employee Commitment: A Conceptual Review in the Nigerian Public Sector - Uchechi Chinazom Ekejiuba; Taiwo Adewale Muritala; Faiza Haruna Maitala; May Ifeoma Nwoye (An Overview on Business, Management and Economics Research Vol. 3, 2023)
In this study, the impact of workplace diversity management on employee engagement in the Nigerian public sector is examined from the perspectives of many academics. The impact of workplace diversity management constructs such as fairness, inclusiveness, equal opportunity, policies, and programs on employee commitment were examined from the perspectives of many specialists. Diversity management is a process intended to create and maintain a positive work environment where the similarities and differences of individuals are valued. The literature on diversity management has mostly emphasized on organization culture; its impact on diversity openness; human resource management practices; institutional environments and organizational contexts to diversity-related pressures expectations, requirements, and incentives; perceived practices and organizational outcomes related to managing employee diversity; and several other issues. One of the current global concerns in many areas is the inconsistent application of workplace diversity management regulations across nations. The fact that only workers from a particular background are treated properly and justly raises the possibility of discrimination. A conceptual review methodology was used in the study, which consulted a number of relevant bodies of literature from numerous respectable publications. However, only research that was published within the last five years was cited in this analysis in order to assure currency. The cited studies, show that fewer articles have been published in recent years. The scholars agreed that diversity management which entails the effort put in place by employers, to ensure unity in diversity was necessary to elicit employee commitment. The findings also revealed that workplace diversity management policies in multicultural nations like Nigeria were poorly implemented even though they existed, and this was reflected in lopsided appointments, promotions, and nominations at the top government level. From the foregoing conclusion, the review recommends that organizations assimilate minorities, integrate diversity and leverage on the variety. For the Nigerian public sector, the review recommends that regulatory bodies such as Federal Character Commission, National Salaries, Income and Wages Commission be made independent and empowered to monitor the government agencies for adherence to the framework of diversity management policies, with the aim of applying penalties for non-compliance while limiting interference in the public agencies. The implementation of this policy will ensure inclusiveness, fairness, and equal opportunity to all citizens.